Spatial Distribution and Utilization of Marine Habitats by Green Turtle (Chelonia mydas) and Hawksbill Turtle (Eretmochelys imbricata) in the Gili Matra Island Marine Protected Area - Lestariningsih, Wiwid Andriyani; Himawan, Mahardika Rizqi; Rahman, Ibadur; Araujo, Gonzalo; Adiwijaya, Cakra; Khaldun, Muhammad Hafidz Ibnu; Cahaya, Himaya Kartika; Alam, Dita Hikmatul; Hotmariyah, Hotmariyah (LPPM Universitas Mataram, 2025)
Sea turtles are one of the key biota in coastal and marine ecosystems whose existence is not only ecologically important, but also holds social, cultural, and economic value. Indonesia, as the largest archipelagic country in the world, is home to six of the world’s seven sea turtle species, making it a globally significant habitat for the sea turtle life cycle. The Gili Matra Marine Protected Area, encompassing the three islands of Gili Trawangan, Gili Meno, and Gili Air, is one of the strategic regions with high potential for sea turtle conservation. This study aims to document and analyze the spatial distribution and habitat use of green turtles (Chelonia mydas) and hawksbill turtles (Eretmochelys imbricata) in the Gili Matra Marine Protected Area. Data collection was carried out during the period of September to October 2024, adjusted to weather conditions and water visibility. The method used was the Underwater Turtle Visual Census Methodology. The composition of sea turtle species and habitat characteristics were analyzed using descriptive analysis to summarize the patterns of species presence, habitat types, and environmental conditions observed during the survey. The findings indicate that the area supports both species, with sea turtles observed at various depths (9–16 meters) across multiple dive sites. The predominance of female individuals and the variation in species presence across sites suggest species specific habitat preferences and potential influences of environmental conditions. Both sea turtle was mostly observed in locations associated with coral reef structures.